Enrique Padilla Aragón. México : desarrollo con pobreza. México : Siglo XXI Editores, 1969. 179 p. - Carrillo Arronte, Ricardo (Estudios Demográficos y Urbanos, 1969)
ENRIQUE PADILLA ARAGÓN, México, desarrollo con pobreza. México, Siglo XXI Editores, 1969.